Влияние модулей Юнга на краевые эффекты в трехслойном цилиндре - Коханенко, Ю.В.; Цирук, С.А.; Величко, Л.Г. ("Доповіді НАН України", 2007)
We study the axisymmetric problem of the theory of end effects for a three-layer cylinder with isotropic layers that is loaded on its end faces by an axial constant load in the exact statement. The influence of Young's moduli of layers on the end effect's length is examined. The inhomogeneous problem of elasticity is solved approximately by the method of finite differences using the concepts of the basic scheme. The analysis of the computed results is carried out.